Síntese hidrotermal de zeólita a partir de rejeitos de caulim da Amazõnia e sua aplicação na adsorção de poluente da indústria têxtil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
In this work, type F zeolitic material with a structure analogous to the mineral called Edingtonite, was synthesized using a kaolin tailing from the city of Vitória do Jarí, in Amapá, as the main source of silicon and aluminum; the starting material and the zeolite F (EDI) phase were characterized by X-ray diffraction (DRX), X-ray fluorescence (FRX) and transmission electron microscopy (MET), being subsequently evaluated for the adsorption capacity by blue of methylene. The synthesis process took place in hydrothermal conditions through static autoclaving and the time-temperature effects, as well as the molar ratios of the alkaline activator KOH were investigated. The results show that in the methodology developed with the kaolin tailings, initially calcined at 700 ° C for 2 hours, then subjected to the reaction in an alkaline medium at 150ºC for 24 hours in the presence of 7.0 g of KOH along with 3.1 g metakaolin; type F zeolite with good crystallinity and with unit cell parameters was obtained with a = b = 9.82 Å, c = 13.04. The adsorption data determined by UV-visible spectrophotometry and adjusted by the Langmuir and Freundlich models suggest that the zeolitic material has a reasonable adsorptive capacity, showing removal efficiency of at most 37%, thus demonstrating to be an alternative and low-cost material for the removal of dyes in aqueous solution in the treatment of industrial effluents.
Keywords: Zeólita f.; Edingtonite; síntese hidrotérmica; caulim; adsorção; CNPQ:: ENGENHARIAS